miRNAs Plasma Profiles in Vascular Dementia: Biomolecular Data and Biomedical Implications - Ragusa, Marco; Bosco, Paolo; Tamburello, Lucia; Barbagallo, Cristina; Condorelli, Angelo G.; Tornitore, Mariangela; Spada, Rosario S.; Barbagallo, Davide; Scalia, Marina; Elia, Maurizio; Di Pietro, Cinzia; Purrello, Michele (Frontiers in Cellular Neuroscience, 2016)
Vascular Dementia (VaD) is a pathogenetically heterogeneous neuropsychiatric syndrome, mainly characterized by cognitive impairment. Among dementias, it is second by incidence after Alzheimer's Dementia (AD). VaD biomolecular bases have been poorly characterized, but vascular-linked factors affecting the CNS and its functions are generally hypothesized to perform a major role, together with cardiovascular and immunological factors. MiRNAs, which perform critically important biomolecular roles within cell networks, are also found in biological fluids as circulating miRNAs (cmiRNAs). We hypothesized that differentially expressed (DE) cmiRNAs in plasma from VaD patients could be applied to diagnose VaD through liquid biopsies; these profiles also could allow to start investigating VaD molecular bases. By exploiting TaqMan Low Density Arrays and single TaqMan assays, miR-10b*, miR29a-3p and miR-130b-3p were discovered and validated as significantly downregulated DE cmiRNAs in VaD patients compared to unaffected controls (NCs). These miRNAs also were found to be significantly downregulated in a matched cohort of AD patients, but miR-130b-3p levels were lower in AD than in VaD. A negative correlation was detected between miR-29a and miR-130b expression and cognitive impairment in VaD and AD, respectively. ROC curves demonstrated that decreased plasma levels of miR-10b*, miR29a-3p and miR-130b-3p allow to discriminate VaD and AD patients from NCs. Furthermore, the concurrent downregulation of both miR-10b* and miR-130b-3p in VaD showed an AUC of 0.789 (p>0.0001) with 75% of sensitivity and 72% of specificity, while an AUC of 0.789 (p>0.0001) with 92% of sensitivity and 81% of specificity was found for both in AD. The miRNAs profiles reported in this paper pave the way to translational applications to molecular VaD diagnosis, but they also should allow to further investigate on its molecular bases.